Influence of coexposure to long working hours and ergonomic risk factors on musculoskeletal symptoms: an interaction analysis - Mo-Yeol Kang; Seong-Sik Cho; Seong-Soo Choi; Jung Il Kim; Jeong Woo Park; JongHyun Hwang (BMJ Open, 2022)
Objectives This study explores the interaction between ergonomic risk factors and long working hours on musculoskeletal symptoms by additive and multiplicative scales.Design We used the data of the fifth Korean Working Condition Survey (KWCS). The KWCS is a cross-sectional study.Setting To represent the entire Korean working population, the probability proportion stratified cluster sampling method was used. The face-to-face interview was carried out with a structured questionnaire.Main outcomes and measures To assess the combined effect of ergonomic risk factors and long working hours on musculoskeletal symptoms, the relative excess risk due to interaction (RERI) and the ratio of ORs were calculated using multiple survey-weighted logistic analysis and postestimation commands.Results The OR for musculoskeletal symptoms was 1.75 (95% CI 1.28 to 1.39) for exposure to long working hours, 3.49 (95% CI 3.06 to 3.99) for exposure to ergonomic risk factors and 5.07 (95% CI 4.33 to 5.93) for coexposure to long working hours and ergonomic risk factors. The RERI was 0.82 (95% CI 0.11 to 1.53) and the ratio of ORs was 0.83 (95% CI 0.50 to 1.14)Conclusion Our findings suggest that coexposure to both ergonomic risk factors and long working hours has a supra-additive interaction effect on musculoskeletal symptoms. Regulations on working hours and workplace interventions might reduce the musculoskeletal diseases of workers.